PENGARUH BEBAN KERJA, KOMPENSASI, DAN KOMUNIKASI TERHADAP KEPUASAN KERJA KARYAWAN PT. NATURAL NUSANTARA (NASA) YOGYAKARTA - Adi Pamungkas; Inayat Hanum Indriati; Anindita Imam Basri (Program Studi Akuntansi, 2022)
The corona virus (Covid-19) that occurred in Indonesia had a big impact on companies, especially in reducing human resources. This causing the burden of workers to be borne by employees increases, decreases in income and poor communication occurs in the company. This study aims to understand the impact of workload, compensation, and communication on job satisfaction. The company used as place of research is PT. Natural Nusantara (NASA) Yogyakarta in March 2021. This study is a type of quantitative research using a sample of 60 respondents. The technique used is saturated sampling, because the total of all the population is the sample. In collecting data through questionnaires, interviews, and observations. The analytical technique used is multiple tinear regression analysis through the SPSS version 21.0 program for windows. The statistics found, prove that segmentally workload has negative and significant effect on job satisfaction based on the regression coefficient level of -0.304 < 0.05. Compensation can effect has a positive and significant on job satisfaction through the value of the regression coefficient as much sig 0.430 > 0.05. While communication can have a positive and significant effect on job satisfaction through the regression coefficient value of sig 0.289 > 0.05. The results of simultaneous testing (Test F) of workload, compensation, and communication can be proven through the Adjusted R Square value of 0.532 (53.2%) with the remaining 0.468 (4.68%) do to other variables not included in this study.